A New Ba0.6Sr0.4TiO3–Silicon Hybrid Metamaterial Device in Terahertz Regime. Issue 19 (23rd March 2016) - Wu, Liang; Du, Ting; Xu, Ningning; Ding, Chunfeng; Li, Hui; Sheng, Quan; Liu, Ming; Yao, Jianquan; Wang, Zhiyong; Lou, Xiaojie; Zhang, Weili
Abstract : Metamaterials, offering unprecedented functionalities to manipulate electromagnetic waves, have become a research hotspot in recent years. Through the incorporation of active media, the exotic electromagnetic behavior of metamaterials can be dramatically empowered by dynamic control. Many ferroelectric materials such as BaSrTiO3 (abbreviated as BST), exhibiting strong response to external electric field, hold great promise in both microwave and terahertz tunable devices. A new active Ba0.6 Sr0.4 TiO3 –silicon hybrid metamaterial device, namely, a SRR (square split‐ring resonator)–BaSrTiO3 thin film‐silicon three‐layer structure is fabricated and intensively studied. The active Ba0.6 Sr0.4 TiO3 thin film hybrid metamaterial, with nanoscale thickness, delivers a transmission contrast up to ≈79% due to electrically enabled carrier transport between the ferroelectric thin film and silicon substrate. This work has significantly increased the low modulation rate of ferroelectric based devices in terahertz range, a major problem in this field remaining unresolved for many years. The proposed BST metamaterial is promising in developing high‐performance real world photonic devices for terahertz technology. Abstract : A giant terahertz modulation is demonstrated in a Ba0.6 Sr0.4 TiO3 (BST)–silicon hybrid metamaterial. These findings are attributed to the absorption of excited free carriers generated from both BST thin film and silicon substrate. This approach can be generalized for use in designing broadband terahertz modulators and switchable terahertz plasmonic devices.